HOXB9 acts as a negative regulator of activated human T cells in response to amino acid deficiency. Issue 6 (1st March 2016) - Hayashi, Keitaro; Ouchi, Motoshi; Endou, Hitoshi; Anzai, Naohiko
Abstract : T‐cell activation is an energy expenditure process and should be properly controlled in accordance with the availability of nutrients such as amino acids to eliminate wasteful energy consumption. However, the details of response to amino acids insufficiency in activated T cells remain largely unknown. Here we show that homeobox B9 (HOXB9), a member of the homeobox gene family that is known as a morphogenesis regulator, acts as a suppressor of activated human T cells to address amino acid starvation. The expression of HOXB9 was triggered by amino acid deprivation as well as functional inhibition of L‐type amino acid transporter 1 (also known as SLC7A5) via activating transcription factor 4 in activated T cells. HOXB9 interfered the activities of NF‐κB, nuclear factor of activated T‐cells (NFAT) and AP‐1 but not retinoic acid receptor‐related orphan receptor, resulting in attenuation of the production of selective cytokines in activated T cells. Thus, the morphogenetic gene plays an unexpected role in the regulation of cellular metabolism with changes in the nutrition status in human T cells.